2018
DOI: 10.1590/18069657rbcs20170250
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the Retention and Availability of Water in Soils of the State of Santa Catarina

Abstract: Soil water retention and availability are important properties for agricultural production, which can be measured directly or estimated by pedotransfer functions. Some studies on this topic were carried out in Santa Catarina, Brazil. To improve the estimates, it is necessary to evaluate other properties, to analyze more soil types, as well as to use other analysis techniques such as artificial neural networks and regression trees. Thus, the objective of the study was to estimate the field capacity (FC), perman… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0
8

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 39 publications
2
7
0
8
Order By: Relevance
“…The field capacity and permanent wilting point estimated values for the soil were 0.53 and 0.29 m 3 m -3 , respectively, which are within the range found in studies for the state of Santa Catarina [22,24]. It was observed that in both years, treatment with water restriction approached and remained partially below permanent wilting point (Figures 2a and b), with the 2019/20 agricultural year being more affected since its treatment without water restriction was compromised.…”
Section: Performance Of the Water Exclusion Systemsupporting
confidence: 84%
“…The field capacity and permanent wilting point estimated values for the soil were 0.53 and 0.29 m 3 m -3 , respectively, which are within the range found in studies for the state of Santa Catarina [22,24]. It was observed that in both years, treatment with water restriction approached and remained partially below permanent wilting point (Figures 2a and b), with the 2019/20 agricultural year being more affected since its treatment without water restriction was compromised.…”
Section: Performance Of the Water Exclusion Systemsupporting
confidence: 84%
“…An SM data assimilation scheme is to simulate dynamic SM at spatiotemporal scales using estimated soil parameters and weather forcing based on a hydrological model [46,47]. The machine learning technique is computationally intensive (e.g., random forest (RF) [48,49], artificial neural network (ANN) [50][51][52][53], support vector regression (SVR) [54][55][56], and regression trees (RT) [57,58]) and used to build mathematical models based on training sets and covariates to extract SM information from the available data [59,60].…”
Section: Introductionmentioning
confidence: 99%
“…The SMLR method was also used to predict soil water infiltration in a dry flood plain of eastern Iran [71], to estimate the plant available water content of unsaturated soil [70]. When the variable of micro-porosity was included to estimate the availability of water in the soil, the SMLR (which features computation efficiency and ease of interpretation) was simpler to use compared with both ANN and RT [58].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Soil water retention prediction is increasing based on soil water stresses from pedotransfer functions by mineral and organic fractions of the soil (BARROS et al, 2013;MEDEIROS et al, 2014). It can be generated for soil water retention curve models (MEDEIROS et al, 2014), or specifically, for certain soil water tensions such as soil water content corresponding to field capacity and permanent wilt point (BORTOLINI; ALBUQUERQUE, 2018;FIDALSKI et al, 2013;MEDEIROS et al, 2014).…”
Section: Introductionmentioning
confidence: 99%